Long-term outcomes of anatomic vs. non-anatomic resection in intrahepatic cholangiocarcinoma with hepatolithiasis: A multicenter retrospective study - Wu, Jun-Yi; Huang, Wen-Tao; He, Wen-bin; Dai, Gao-Fan; Lv, Jia-Hui; Qiu, Fu-Nan (Frontiers in Medicine, 2023)
Background The benefits of anatomic resection (AR) vs. non-anatomic resection (NAR) in patients with primary intrahepatic cholangiocarcinoma (ICC) with hepatolithiasis (HICC) are unclear. This study aimed to compare the long-term outcomes of AR vs. NAR in patients with HICC. Methods A total of 147 consecutive patients with HICC who underwent R0 hepatectomy were included. Overall survival (OS) and recurrence-free survival (RFS) following AR vs. NARs were compared using a 1:1 propensity score matching (PSM) analysis. A subgroup analysis was also conducted according to whether there are lymph node metastases (LNM). Results In a multivariate analysis, CA 19-9 (>39 U/L), microvascular invasion, LNM, and NAR were independent risk factors for poor RFS and OS rates, whereas multiple tumors were independent risk factors for OS. AR had better 1-, 3-, and 5-year RFS and OS rates than NAR (OS: 78.7, 58.9, and 28.5%, respectively, vs. 61.2, 25.4, and 8.8%, respectively; RFS: 59.5, 36.5, and 20.5%, respectively, vs. 38.2, 12.1, and 6.9%, respectively). After PSM, 100 patients were enrolled. The NAR group also had significantly poorer OS and RFS (OS: 0.016; RFS: p = 0.010) than the AR group. The subgroup analysis demonstrated that in HICC without LNM, OS and RFS were significantly poorer in the NAR group than the AR group, while no significant differences were observed in HICC with LNM before or after PSM. Conclusion Anatomic resection was associated with better long-term survival outcomes than NAR in patients with HICC, except for patients with LNM.